Monoclonal antibody-based capture ELISA in the diagnosis of previous dengue infection - Sirivichayakul, Chukiat; Limkittikul, Kriengsak; Chanthavanich, Pornthep; Yoksan, Sutee; Ratchatatat, Anuttarasakdi; Lim, Jacqueline Kyungah; Arunsodsai, Watcharee; Sabchareon, Arunee (Virology journal, 2019)
Dengue is an important mosquito-borne disease. There is currently only one licensed vaccine for dengue prevention. The vaccine provides higher efficacy in pre-vaccination dengue-seropositive persons but a higher risk of subsequent more severe dengue in dengue-seronegative persons. It is recommended that the dengue vaccine may be given in dengue-seropositive individuals or as mass vaccination without individual pre-vaccination screening in areas where the dengue seroprevalence is > 80% in children aged 9 years. We evaluated a dengue specific immunoglobulin G monoclonal antibody-based capture enzyme-linked immunosorbent assay (MAb-ELISA) in the diagnosis of previous dengue infection using serum samples from the cohort study in Ratchaburi Province, Thailand. The MAb-ELISA was compared to 70% plaque reduction neutralization test (PRNT70) in 453 serum samples from children aged 3-11 years in Ratchaburi Province, Thailand. The sensitivity and specificity of MAb-ELISA at the positive to negative (P/N) ratio cut-off level of > 3 were both 0.91 in the diagnosis of previous dengue infection, compared to PRNT70. The false positivity was mainly in Japanese encephalitis (JE) seropositive subjects. This research provides evidence that MAb-ELISA is useful for dengue seroprevalence study and dengue pre-vaccination screening. JE seropositivity was the major cause of false positive result in the study population.